A Fistful of Mars Exploring the Role of Martian Meteorites in Cultural Heritage and Scientific Inquiry - Annarita Franza; Xhonatan Shehaj; Giovanni Pratesi (Heritage)
Meteorites have intrigued humanity for centuries, representing our enduring pursuit of knowledge and exploration of the cosmos’ enigmas. These celestial objects have not only influenced artistic expression and the formation of myths but have also fostered scientific inquiry. In this regard, meteorites are crucial to space research, offering valuable information about the early solar system, the formation of planets, and the development of organic compounds. Their analysis aids in deciphering cosmic processes and identifying resources that may support future space missions, making them essential for advancing planetary sciences. Meteorites are also cultural heritage items, with most known samples preserved in natural history museums. This paper deals with the Martian meteorites collected to date, focusing on NWA 16788, the largest individual Martian meteorite recovered so far.